Foliar Application of Green Synthesized Zinc Sulphide and Zinc Oxide Nano Particles Enhances Growth, Root Attributes, Yield and Oil Quality of Sunflower (Helianthus annuus L.) (Global Journal of Science Frontier Research, 2019)
A balanced nutrition for enhanced nutrient use efficiency is important to achieve potential crop yield. A deficiency of secondary and micronutrients is known to impair growth and quality of oil seed crops such as sunflower. The present study examined the effect of foliar application of nano-scale zinc particles in combination with boron on the growth and yield attributes of sunflower cv. RFSH-130 in a controlled environment. The treatments comprised foliar application of different nanoparticles (ZnS @ 400 ppm and ZnO @ 1000 ppm) and conventional ZnSO 4 @ 5000 ppm at 35 and 55 DAS. Further, these were combined with or without spray of boron @ 0.5% at 40 DAS. The sizes of the green synthesized nanoparticles of ZnS and ZnO in the presence of a biopolymer, chetosan were 60 and 38 nm respectively. ZnS and ZnO in nano formulations were absorbed by sunflower foliage to a greater extent compared to bulk ZnSO 4 . The results revealed that green synthesized ZnS and ZNO nanoparticles enhanced the growth and yield of sunflower.
Keywords: sunflower; nano ZnO; nano ZnS; NPs; FE-SEM; XRD; boron; ZnSO4; foliar spray